Temporal Stability and Genetic Diversity of 48-Year-Old T-Series Phages - Dinesh Subedi (mSystems, 2021)
T-series bacteriophages have been used throughout the world for various molecular biology researches, which were critical for establishing the fundamentals of molecular biology, from the structure of DNA to advanced gene-editing tools. These model bacteriophages help keep research data consistent and comparable between laboratories.